The japanese lover eaudiobook - Allende, Isabel (Simon & Schuster Audio, 2015)
From New York Times bestselling author Isabel Allende, "a magical and sweeping" ( Publishers Weekly , starred review) love story and multigenerational epic that stretches from San Francisco in the present-day to Poland and the United States during World War II. In 1939, as Poland falls under the shadow of the Nazis, young Alma Belasco's parents send her away to live in safety with an aunt and uncle in their opulent mansion in San Francisco. There, as the rest of the world goes to war, she encounters Ichimei Fukuda, the quiet and gentle son of the family's Japanese gardener. Unnoticed by those around them, a tender love affair begins to blossom. Following the Japanese attack on Pearl Harbor, the two are cruelly pulled apart as Ichimei and his family—like thousands of other Japanese Americans—are declared enemies and forcibly relocated to internment camps run by the United States government. Throughout their lifetimes, Alma and Ichimei reunite again and again, but theirs is a love that they are forever forced to hide from the world. Decades later, Alma is nearing the end of her long and eventful life. Irina Bazili, a care worker struggling to come to terms with her own troubled past, meets the elderly woman and her grandson, Seth, at San Francisco's charmingly eccentric Lark House nursing home. As Irina and Seth forge a friendship, they become intrigued by a series of mysterious gifts and letters sent to Alma, eventually learning about Ichimei and this extraordinary secret passion that has endured for nearly seventy years. Sweeping through time and spanning generations and continents, The Japanese Lover is written with the same keen understanding of her characters that Isabel Allende has been known for since her landmark first novel The House of the Spirits . The Japanese Lover is a moving tribute to the constancy of the human heart in a world of unceasing change.